Exploring typologies of consultation performance using authentic clinical experiences to support learning and assessment in postgraduate medical training. Issue 7 (July 2022) - Timmerman, Angelique; Oerlemans, Marjolein; van der Vleuten, Cees; Pawlikowska, Teresa; Ram, Paul; Muris, Jean
Abstract: Objective: To validate and refine typologies of consultation performance from previous research to identify learning needs associated with each typology. Methods: We performed a qualitative study in a General Practice Specialty Training programme, using a two-stage design. First, we selected four exemplars from 80 videotaped consultations of 7 first-year and 6 third-year trainees that reflected the four typologies. We subsequently held individual interviews with clinical supervisors (N = 20) who observed these consultations to identify recurrent trainee behaviours. Results: The 'doctor-patient interaction' dimension from previous research was specified to encompass relationship-building, exploring, structuring, and shared decision-making competencies. Medical expertise was a moderating factor. The attitude and consultation behaviours included in the typologies were validated and we formulated directions for learning based on learning needs identified per typology. Conclusion: Supervisors have a shared frame of reference for the behaviours reflecting proficient consultation performance. Serving as a developmental road map, all learning needs emphasised contextual adaptation, calling for an improved balance between patient-centred relationship building and application of medical expertise. Practice implications: By providing rich and tailored feedback on consultation performance, the refined typologies – albeit subject to additional refinement in future research – may promote the monitoring of individual competence development over time. Highlights: Skilled consultation performance requires contextual adaptation. Clinical supervisors consistently outline what proficient performance entails. Learning needs addressing contextual adaptation provide a developmental road map. Narrative profiles support monitoring and tailored feedback on individual learning.